Moving stories: precarious work and multiple migrations - Mcdowell, L (Routledge, 2018)
According to the United Nations over 3% of the global population or 232 million people currently live outside their country of birth. Their significance as a growing proportion of the labour force in many European countries is widely known. It is also evident that women – many of them young – are increasingly represented among economic migrants and asylum seekers. However, the longer term contribution of women, as migrants and as workers, is less well recorded. Here, I explore the connections between migration and employment, through the lens of oral histories undertaken with women who moved to the UK. Their life stories illustrate the growing diversity among female migrants as well as the changing nature of women’s employment. My key focus is, however, not on the work these women migrants undertook in the UK, but on precarious forms of waged work engaged in during the migration journey itself. I also reflect on oral history as a method and the problems of writing difference for feminist scholars working with and on women migrants.